Modern Approaches to the Preparation System of Masters in eSports - Oksana Shynkaruk; Nataliia Byshevets; Olena Iakovenko; Kostyantyn Serhiyenko; Eduard Anokhin; Yuriy Yukhno; Vitaly Usychenko; Maksym Yarmolenko; Sergiy Stroganov (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2021)
The preconditions of the development of eSports are investigated and the content of Masters' preparation in eSports is substantiated. Analysis of scientific and methodological literature, Internet data and methods of mathematical statistics were used as research methods. The study involved 15 experts: eSports specialists, rep- resentatives of the Ukrainian eSports Federation. The research was conducted during of the 2019-2020. The analysis of the curriculums of the second level of post-graduate studies of 6 higher educational institutions of foreign countries was carried out. The analysis allowed identifying promising areas of eSports development in the educational environment. The main preconditions for its development with the projected benefits of eSports have been identified, potential threats have been identified, including problems with the locomotor system, decreased visual acuity, and deteriorating health due to irrational work schedule. The necessity of master's programs introduction for preparation of specialists in eSports is justified. It is established that along with the special practical skills of the player, eSports specialists must clearly understand the aspects of team building and organization of the eSports training process, as well as have theoretical knowledge, practical skills and abilities aimed at maintaining and improving their health. The terminology for ensuring the devel- opment of eSports science is clarified. The educational program of the second level of post-graduate studies of higher education specialty 017 "Physical Culture and Sports", specialization eSports was developed. Accord- ing to the results of the expert evaluations method the content of the specialization cycle of the educational program was determined.